2013
DOI: 10.1111/nph.12642
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a proton‐coupled vacuolar glucose exporter impairs freezing tolerance and seed germination

Abstract: SummaryArabidopsis vacuoles harbor, besides sugar transporter of the TMT-type, an early response to dehydration like 6 (ERDL6) protein involved in glucose export into the cytosol. However, the mode of transport of ERDL6 and the plant's feedback to overexpression of its activity on essential properties such as, for example, seed germination or freezing tolerance, remain unexplored.Using patch-clamp studies on vacuoles expressing AtERDL6 we demonstrated directly that this carrier operates as a proton-driven gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 47 publications
(103 reference statements)
10
83
1
Order By: Relevance
“…Recently, Gong et al (2015) reported that AtSUC2 and AtSUC4 were induced by cold and loss-of-function mutations resulted in hypersensitive responses to abiotic stress. Additionally, most cold-induced transporters are positively correlated with plant cold tolerance via the modulation of sugar allocation, such as MfINT-like (Sambe et al 2015), BvIMP (ERD6-like) (Klemens et al 2013b) and AtTMTs (Schulze et al 2012;Wormit et al 2006), suggesting that the up-regulated genes in the tea plant could exhibit similar functions as their homologous genes.…”
Section: Sugar Transporters Mediate Sugar Allocation In Response To Cmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, Gong et al (2015) reported that AtSUC2 and AtSUC4 were induced by cold and loss-of-function mutations resulted in hypersensitive responses to abiotic stress. Additionally, most cold-induced transporters are positively correlated with plant cold tolerance via the modulation of sugar allocation, such as MfINT-like (Sambe et al 2015), BvIMP (ERD6-like) (Klemens et al 2013b) and AtTMTs (Schulze et al 2012;Wormit et al 2006), suggesting that the up-regulated genes in the tea plant could exhibit similar functions as their homologous genes.…”
Section: Sugar Transporters Mediate Sugar Allocation In Response To Cmentioning
confidence: 96%
“…8b, c), but these genes might differ from the SWEET types under cold stress. Recently, Klemens et al (2013b) identified a ERD6-like transporter gene from the sugar beet and showed that its expression was inhibited by cold stress, and overexpression of ERD6 in Arabidopsis led to reduced frost tolerance. However, the ability to transport sugar in response to cold is not only dependent on mRNA abundance but on control via protein modifications, such as phosphorylation (Schulze, et al 2012).…”
Section: Sugar Transporters Mediate Sugar Allocation In Response To Cmentioning
confidence: 99%
“…ERDL6 was recently characterized as a novel dehydration-induced glucose exporter [68]. The Arabidopsis mutant of this transporter displayed a considerable increase in seed weight as a consequence of elevated levels of seed sugars, proteins, and lipids [68], whereas plants overexpressing this transporter were recently demonstrated to display impaired freezing tolerance and seed germination [69]. Mutants of the inositol proton transporter develop very short roots, a phenotype that could be rescued by inositol feeding and that appears to be due to a shortage of precursors for lipid or inositol phosphate signaling [70].…”
Section: Box 1 Starch-related Cytosolic Heteroglycansmentioning
confidence: 99%
“…The precise function of most of the non-sucrose long-distance transport pathways is currently not well characterized; however, the isolation and biochemical characterization of many transport proteins have recently been documented (see for example [96,97]). Furthermore, reverse genetic experimentation has recently begun to shed light on the importance of some of these pathways [69,98], suggesting that we will shortly be able to assess their relative importance under a range of (a)biotic challenges.…”
Section: Box 2 Intracellular Transport Of Sugar Alcohols and Oligosamentioning
confidence: 99%
“…At the vacuolar membrane, the MST subfamilies, vacuolar glucose transporter (vGT), and tonoplast membrane transporter (TMT) function as sugar/H+ antiporters that load sugars into the vacuole (Wormit et al, 2006; Aluri and Büttner, 2007; Schulz et al, 2011). Proteins of the MST subfamily of ERD six-like transporters (ERD6 or ESL1) are likely involved in energy-independent sugar efflux from the vacuole (Poschet et al, 2011; Klemens et al, 2014). …”
Section: Introductionmentioning
confidence: 99%